Penerapan Teknik Data Mining terhadap Prediksi Pemilihan Jurusan IPA/IPS Siswa Menggunakan Algoritma C4.5 : Penerapan Teknik Data Mining terhadap Prediksi Pemilihan Jurusan IPA/IPS Siswa Menggunakan Algoritma C4.5 - Jean Rahmatika Jhody; Muhammad Ramadhan Tanjung; Snowhart Novolulu (Institut Riset dan Publikasi Indonesia, 2023)
The selection of science (IPA) or social studies (IPS) majors is a crucial decision in a student's educational journey with significant implications for their academic and career development. This research discusses the implementation of data mining techniques using the C4.5 algorithm to predict the choice of IPA or IPS majors by students. The research results indicate that the most influential attribute in students' major selection is their National Examination (UN) scores. By employing the C4.5 algorithm, students with specific UN scores are categorized into either the IPA or IPS group. In data testing using RapidMiner, the analysis confirms the effectiveness of the C4.5 algorithm in predicting students' major choices. With the assistance of data mining technology, the data analysis process becomes more efficient, providing valuable insights for educational decision-making. This research makes a significant contribution to the development of more effective and efficient educational recommendation systems.